Band gap behaviour of optimal one-dimensional composite structures with an additive manufactured stiffener. (15th November 2018) - Ampatzidis, T.; Leach, R.K.; Tuck, C.J.; Chronopoulos, D.
Abstract: In this work, the banded behaviour of composite one-dimensional structures with an additive manufactured stiffener is examined. A finite element method is used to calculate the stiffness, mass and damping matrices, and periodic structure theory is used to obtain the wave propagation of one-dimensional structures. A multi-disciplinary design optimisation scheme is developed to achieve optimal banded behaviour and structural characteristics of the structures under investigation. Having acquired the optimal solution of the case study, a representative specimen is manufactured using a carbon fibre cured plate and additive manufactured nylon-based material structure. Experimental measurements of the dynamic performance of the hybrid composite structure are conducted using a laser vibrometer and electrodynamic shaker setup to validate the finite element model.